KUALITAS GURU SEKOLAH DASAR STUDI PERBANDINGAN ANTARA SUMATERA DENGAN JAWA (Analisis Data Survei Governance dan Desentralisasi 2 2006) - SIBUEA, HARMADA JUNIANTO; PARTINI, PARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The quality of teachers lately has increasingly gained attention. In addition to its being the largest component of the education budget to absorb, as well as the quality is considered low. The low quality of education at this time was even called as a result of the poor quality of teachers. This study used data Governance and Decentralization Survey-2 in 2006 with the selection of the location in Java and Sumatra. The purpose of this study was to analyze the quality, sociodemographic characteristics and qualifications of primary school teachers as well as to analyze the factors that affect the quality of teachers in Sumatra and Java. Teacher quality is built of six components: creative teaching, teaching innovation, teaching preparation, use of tools and examples in teaching, teachers' attention to student absenteeism and teacher communication with parents. The analysis technique used is descriptive analysis and bivariate analysis using chi-square test (Ï2). Results of this study found that the quality of teachers in Sumatra and Java in general is still low, especially in terms of creativity and innovation of teaching, lack of teacher preparation that tends to repeat the lessons of yesteryear as well as the lack of communication with parents teachers built. Elementary teacher excellence in Sumatra and Java is in the use of tools and examples to facilitate students 'understanding of teaching materials and teachers' awareness of the absence of students in the class. The quality of primary school teachers in Java is generally better than in Sumatra, especially in terms of creativity and innovation of teaching and concern for student attendance. While elementary school teachers in Sumatra better in terms of allocation of time for teaching preparation. Human capital and social capital as an important capital improvement of the quality of teachers has not been fully utilized by the teacher. Low education and training accounts for the poor quality of teachers. While income and experience of teachers do not have a significant impact on the quality of teachers, especially elementary teachers in Sumatra. Social networks are institutionalized in the form of KKG are not utilized to improve quality. Poor adherence to the norms of teacher preparation teachers teach teaching resulted in low quality.